PENERAPAN PICTURE EXCHANGE COMMUNICATION SYSTEM (PECS) DALAM MENINGKATKAN KOMUNIKASI VERBAL ANAK AUTISM SPECTRUM DISORDER (ASD) - Anwar Dani, Robik (Widya Warta, 2018)
The objective of this research was to examine the effectiveness of Picture Exchange Communication System (PECS) for increasing verbal communication of children with Autism Spectrum Disorder (ASD). Single-case research method with A-B-A design was applied in this research. The subjects of the experiment were children aged seven until eight years old studying in a pre-school in Semarang diagnosed with Autism Spectrum Disorder (ASD). A verbal communication behavior checklists were used for data collecting in this experiment. The measurement was taken as follows: at the baseline one, the treatment, and the baseline two. Descriptive quantitative analysis method was used for data analysis. The results of data analysis showed that the verbal communication scores of the subject increased. In conclusion, the Picture Exchange Communication System (PECS) increases verbal communication of children with Autism Spectrum Disorder (ASD).